(3fRgI GdXQaGA hJMaI GdNdaGAs - (3YHGS Hf Ydj Hf OGhO Hf GdeXaQ jhSa GdQShdj GdZSGfj, Gdedc GdCaVd , J (B778 (3g` s ((3SdjeGf Hf MSjf Hf LGfe s)
(3ChdgG (B:s
(3hHYO, agPG eNJUQ jTJed Ydi QShe GdNdaGA hBOGH NOeJge hGdJMjI hGdSdGe Ydjge s
(3BNQgG (B:s
"(3bd gd jSJhj GdPjf jYdehf hGdPjf dG jYdehf EfeG jJPcQ ChdhG GdCdHGH(B" (3hgPG BNQ eG YfjfG Hg ef LeY gPG GdeNJUQ Ydi MSH GdEecGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3hGdNW ajg HYV GdVHWs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B262 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B61s
Keywords: (3GdCOHs